Revolusi Keamanan Berkendara : Sistem Keselamatan Berbasis Mikrokontroller - Hadian Mandala Putra; Akbar, Taufik; Hafifan Triadi Putra, Ahmad; Ida Wahidah; Suhartini (Fakultas Teknik Universitas Hamzanwadi, 2024)
The increasing need for transportation, especially motorcycles, has led to many illegal methods and criminal actions by individuals committing motorcycle theft. Fundamentally, security and safety are the primary concerns motorcycle users must pay attention to on the road. Many vehicle users neglect safety while riding, such as inappropriate driving. Some actions endanger themselves and other drivers, like using a cell phone while riding, causing the rider to lose focus. Therefore, this research offers a solution as a microcontroller-based security and safety system aimed at minimizing motorcycle theft and improving riding safety. The solution from this research is to produce a microcontroller-based technology utilizing RFID for security, touch sensors, and push buttons for safety when the rider does not follow proper riding procedures. The Research & Development method is used in this research, with five stages: analysis, design, development, implementation, and evaluation. The results of this study are a prototype of a security and safety system based on an Arduino Uno microcontroller as the control center. Regarding security, the vehicle starts only with registered access in the control center, which is then placed on the RF reader installed on the car. From the test results, using an e-KTP as the vehicle access medium successfully started the motorcycle with a 0% error rate from 10 trials. Regarding rider safety, using a touch sensor to test the number of passengers was successful, with an 80% success rate from 10 trials. The push button succeeded with a 100% success rate from 10 trials when users did not position their hands on both motorcycle handles (bars) and successfully triggered the alarm when the rider was not riding correctly.